Efficacy of highly selective M-cholineblocker hyoscine butylbromide at patients with chronic pancreatitis - V. B. Grinevich; Ye. I. Sas; N. N. Scherbina; F. A. Karyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study clinical efficacy of highly selective M-cholineblocker hyoscine butylbromide (buscopan) in patients with chronic pancreatitis (CP), to estimate its effect on myoelectric activity, рН of the upper regions of gastro-intestinal tract (GIT), and also on dynamics of quality of life of the patients.Material and methods. The study group included 54 patients with CP, of them 40 (74,1%) had primary pancreatitis and 14 (25,9%) – biliary pancreatitis. Besides traditional methods of investigation electrogastrointestinography, transendoscopic topical express pH-metry with positioning of potential electrodes in the esophagus, body, antral region of the stomach and duodenum were carried out. Quality of life of patients estimated by SF-36 questionnaire.Results. Application of hyoscine butylbromide within complex treatment of CP (basic group) allows to achieve significant increase of activity and improvement of state of health of patients (by visual-analog scale) along relief of abdominal pain and dyspeptic symptoms. On a background of remission achievement in group of the patients receiving hyoscine butylbromide, in comparison to control group quality of life by such scales as PF, BP, GH, MH significantly increased, while in comparison group – only by ВР scale. In basic group statistically significant decrease of the stomach, duodenum and jejunum tone was marked that provided increase of functional volume of the stomach and jejunum.Conclusions. Hyoscine butylbromide has physiological influence on secretory function of GIT and is capable to eliminate selectively motor disorders of its upper regions – duodenum and jejunum that determines rate of CP remission achievement. Ability of this drug to reduce effictively acid production and positively influence scores of quality of life of patients defines good prospects of its application in complex treatment of chronic pancreatitis of mild and average severity.